The application of multi-criteria analysis to decision support for the facility management of a residential district - Vilutienė, Tatjana; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2003)
The article deals with the problem of dwelling maintenance. In this paper the process of building maintenance in Lithuania is analysed, the activities of subjects carrying out maintenance work described, and a comparison of maintenance variants was made applying the methods WSM, WPM, AHP, Revised AHP and Topsis. A method of multi- criteria complex proportional evaluation of the projects was also applied for determining the efficient variant and the degree of its utility. The analysis of the application of the multi-criteria methods for solving the problems with multiple objectives was also made. In striving to prolong the existence of buildings the professional use of a property should be ensured. The article presents a model of property management with the participation of monitoring organisations. This model helps ensure a more effective facilities management process and the work quality in dwellings. First Published Online: 26 Jul 2012